Manajemen Laba Melalui Aktifitas Riil Terhadap Koefisien Respon Laba - SAPTA SETIA DARMA (Universitas Pamulang, 2017)
The objective of this research is to examine and analyze the impact of companies applying earnings management through real activities, both simultaneously and partially, toward earnings response coefficient. This research was conducted as a response that to detect earnings management can do through real acitivities that consist of five methods of measurement; abnormal cash flow from operation, abnormal cost of good sold, abnormal discretionary expenses, abnormal inventory and abnormal production cost (Roychowdhury, 2006). The population consists of manufacturing companies listed on the Indonesia Stock Exchange during period of 2011-2013. Samples members of 132 companies are selected using purposive sampling method.The result of regression analysis indicated that partial abnormal cost of goods sold significant positive effect on earnings response coefficient, which received H2. Abnormal cash flow from operation, abnormal cost of good sold, abnormal discretionary expenses, abnormal inventory and abnormal production cost affect earnings response coefficient